Comparison of Myoelectric Activity of a Selection of Upper Extremity Muscles while Doing Bench Press in Two Training Methods of TRX and Barbell Bench Press - Ahmad Reza Zibaei; Heydar Sadeghi; Mahdi Baghaeian (Biyumikānīk-i varzishī, 2016)
Objective: The aim of present research is to compare the myoelectric activity of some chosen upper extremity muscles while doing bench press in two training methods of TRX and barbell bench press. Methods: Ten physically healthy students of physical education with experience in TRX participated in the study. Electromyography Bio Vision sixteen-channel and surface electrodes were used to calculate muscle activity of pectoralis major, anterior deltoeid, triceps brachii and trapezius. Data analysis of variance with repeated measures was used to assess the difference between the three states of the experiment at p<0/05. Results: After performing the relative tests following results were obtained: the activity rate of dolly anterior muscle in TRX(b) method compared to barbell bench press 85% (P=0.015) and TRX(a) 66% decreased meaningfully (P=0.017). However, there were no meaningful difference, between barbell bench press and TRX(a) (P=0.65), the activity rate of pectoralis major muscles in barbell bench press increased by (P=0.000) as compared with 200% (P=0.000) for TRX(b). The activity rate of the triceps brachii in barbell bench press method increased by 185% as compared with TRX(b) (P=0.023). Compared to average ratings of trapezius muscle, it was found that TRX(a) would have the highest rating and the barbell bench press has the lowest and it was also observed that barbell bench press has less electrical activity compared to TRX(a) and TRX(b) methods. Conclusion: Considering these results it can be maintained that TRX bench press resistance training can be an alternative and effective practice for barbell bench press because, given the results, it can be appreciated that TRX bench press, dips low in the trunk, can lead to muscle activity close to the level of muscle activity during the barbell bench press drill.